2015
DOI: 10.1128/mbio.00037-15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Upper Respiratory Tract Microbiotas as the Source of the Lung and Gastric Microbiotas in Healthy Individuals

Abstract: No studies have examined the relationships between bacterial communities along sites of the upper aerodigestive tract of an individual subject. Our objective was to perform an intrasubject and intersite analysis to determine the contributions of two upper mucosal sites (mouth and nose) as source communities for the bacterial microbiome of lower sites (lungs and stomach). Oral wash, bronchoalveolar lavage (BAL) fluid, nasal swab, and gastric aspirate samples were collected from 28 healthy subjects. Extensive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
625
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(677 citation statements)
references
References 45 publications
39
625
0
13
Order By: Relevance
“…A culture-based study in healthy adults supports this finding, as the bronchial fraction had a greater diversity and higher concentrations of normal respiratory flora than the alveolar fraction (Rasmussen et al, 2001). In a second microbiome study, sequential BAL specimens were obtained from two lobes, with no significant difference in bacterial community composition, and the authors concluded that sampling of the lungs by bronchoscopy was not confounded by oral microbiome contamination (Bassis et al, 2015). In our study, generally more bacteria were recovered from the first lavage when measured by proportions with lower-airway infection or mean growth scores.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…A culture-based study in healthy adults supports this finding, as the bronchial fraction had a greater diversity and higher concentrations of normal respiratory flora than the alveolar fraction (Rasmussen et al, 2001). In a second microbiome study, sequential BAL specimens were obtained from two lobes, with no significant difference in bacterial community composition, and the authors concluded that sampling of the lungs by bronchoscopy was not confounded by oral microbiome contamination (Bassis et al, 2015). In our study, generally more bacteria were recovered from the first lavage when measured by proportions with lower-airway infection or mean growth scores.…”
supporting
confidence: 56%
“…ml 21 ), suggesting colonization of the lower airways rather than contamination. The healthy lung is no longer considered to be sterile, with evidence suggesting it may harbour its own unique microbiome (Bassis et al, 2015;Charlson et al, 2011). Bacterial communities from the healthy lung largely reflect upper respiratory tract (URT) organisms, in particular from the oral rather than the nasal cavity, with Streptococcus being among the prominent genera (Bassis et al, 2015;Charlson et al, 2011).…”
mentioning
confidence: 99%
“…The microbiome harbored by the bronchial tree and the oropharynx have a close similarity in the healthy subject, mainly due to aspiration of oropharyngeal secretions during sleep (8,9). The local environment of the bronchial tree and the lung is able to modify the microbiome after the aspiration of secretions, however, as shown by the higher relative abundance of specific OTUs part of the Prevotella genus in respiratory samples (9).…”
Section: The Respiratory Microbiomementioning
confidence: 99%
“…While for decades we could rest assured that the only microbially colonised niches seemed to be our digestive system and the skin, there is now hardly any part of our bodies indeed not inhabited by microbes. This includes nasal and auditory cavities, hair follicles and sweat glands, the respiratory and the urogenital tract systems and might even include dormant remainders of infections circulating in our blood system (Bassis et al 2015;Callewaert et al 2014;Costello et al 2009;Potgieter et al 2015;Thomas-White et al 2016). In short, apparently anything that can be reached and attached to in the human body becomes colonised by bacteria.…”
mentioning
confidence: 99%